2003
DOI: 10.1080/00750770309555815
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in Ireland‐ recent trends in temperature and precipitation

Abstract: This paper presents an assessment of indicators of climate change in Ireland over the past century. Trends are examined in order to determine the magnitude and direction of ongoing climate change. Although detection of a trend is difficult due to the influence of the North Atlantic Ocean, it is concluded that Irish climate is following similar trajectories to those predicted by global climate models. Climatic variables investigated included the key temperature and precipitation data series from the Irish synop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
3
21
1
1
Order By: Relevance
“…Our conclusions here are broadly in accordance with those of McElwain and Sweeney (2003), which were based on data from a number of sites in Ireland over a shorter period since 1890.…”
Section: Seasonal Meanssupporting
confidence: 81%
“…Our conclusions here are broadly in accordance with those of McElwain and Sweeney (2003), which were based on data from a number of sites in Ireland over a shorter period since 1890.…”
Section: Seasonal Meanssupporting
confidence: 81%
“…It has been shown that air temperature, precipitation, cloud cover, wind velocity and relative humidity are all positively correlated to NAO index values (Jennings et al 2000). This mode of natural variability is most prevalent during the winter months (McElwain and Sweeney 2003), and inter-decadal change is exhibited on irregular timescales (Hurrell 1995, Hurrell andDeser 2009). NAO variability and its influence on winter climate in Irish long-term records have been previously investigated Sweeney 2007, Galvin et al 2011).…”
Section: Temperature Context For Irelandmentioning
confidence: 99%
“…Current trends in Irish temperature closely follow global patterns, with numerous studies having focused on climate amelioration at the beginning of the twentieth century and the accelerated warming since the 1990s (Vincent and Gullet 1999, Zhai and Ren 1999, McElwain and Sweeney 2003, 2007. Two main warm intervals have been widely acknowledged in Irish climate literature: 1910Á1945 and 1978Ápresent (McElwain and Sweeney 2003.…”
Section: Temperature Context For Irelandmentioning
confidence: 99%
See 2 more Smart Citations